Aspectos epidemiológicos de agentes virais em caprinos de diferentes mesorregiões fisiográficas do nordeste brasileiro - Sousa, Maximiana Mesquita de (Universidade Federal Rural do Semi-Árido, 2018)
Goat breeding in the Northeast is mainly due to the size of the herd. Considered an important alternative of work and income for family agriculture, it can be a strong allied to the fixation of the man in the field. However, sanitary order trouble compromise the productivity and success of the activity. In this context, the aim of this study was to determine the epidemiological aspects of viral agents causing Bluetongue Virus and Caprine Arthritis Encephalitis, in goats of different physiographic mesoregions of Northeast Brazil. For the research of antibodies against Blue Language, 1460 serum samples from 110 producing units from the states of Maranhão, Piauí, Alagoas and Sergipe were analyzed through the Elisa of competition. The prevalence found in the Sertão de Alagoas was 1.8% (03/168), Sergipe (Agreste 20.0% (31/155), Sertão 12.9% (20/155), Piauí (Southwest 72.2% (234/324), North Center 56.9% (147/258) and Maranhão (East 65.7% (100/152), North 43.1% (107/248). In the research for anti-CAEV antibodies, through Western Blotting, on average two breeder by nurser were examined, totaling 513 serum samples and 251 properties. The prevalence found was 6.2% (32/513). In each participating state of the study, the following prevalences were found: Piauí 5.8% (7/119), Maranhão 2.0% (01/48), Sergipe 7.1% (03/42), Alagoas 17, 6% (03/17), Rio Grande do Norte 4.7% (05/105), Paraíba 2.1% (02/94) and Ceará 12.5% (11/34). Therefore, the results obtained allow us to conclude that the two diseases studied are present in the herds of the Northeast, being necessary to implement measures of control and prophylaxis aimed at reducing their of dissemination
Keywords: CAE; caprinos; Língua Azul; prevalência de anticorpos; CAE; goats; bluetongue; prevalence of antibodies; CIENCIAS AGRARIAS::MEDICINA VETERINARIA